A Rare Case of Acute Myocardial Infarction due to Coronary Artery Dissection and Heparin-Induced Thrombocytopenia - Michael G. Fradley; Douglas E. Drachman (Case Reports in Medicine)
Although both coronary artery dissection and heparin-induced thrombocytopenia may provoke myocardial infarction, it is extremely rare for both conditions to develop simultaneously in a single patient. We report a case of a 69-year-old woman who sustained a head-on motor vehicle accident with associated chest trauma. During a subsequent hospitalization, she was exposed to subcutaneous heparin and developed significant thrombocytopenia. Shortly thereafter, she re-presented with an acute myocardial infarction. Coronary angiography revealed a spiral dissection with superimposed thrombosis within the right coronary artery, while laboratory testing confirmed the diagnosis of heparin induced thrombocytopenia. She was treated with catheter-based thrombectomy and adjunctive direct thrombin inhibitor therapy, followed by three months of systemic anticoagulation with warfarin. To our knowledge, this represents the first published case of a native vessel myocardial infarction due to the combination of coronary artery dissection and heparin-induced thrombocytopenia.